Structural Health Monitoring of an Historical Building: The Main Spire of the Duomo Di Milano. Issue 4 (19th May 2017) - Cigada, A.; Corradi Dell'Acqua, L.; Mörlin Visconti Castiglione, B.; Scaccabarozzi, M.; Vanali, M.; Zappa, E.
ABSTRACT: Health assessment of historical buildings by means of monitoring systems is for sure a fundamental step to preserve architectural heritage, especially for countries as Italy, rich in ancient monuments. Events such as earthquakes or severe weather phenomena constitute a major risk for these buildings because of their age and the related weakness to sustain exceptional excitations. The availability of a continuous, real-time, and automatic structural health monitoring system is considered a useful tool for early detection of a potentially dangerous situation for the structure and its occupants. The choice of the best measurement strategy provided by the monitoring system is crucial: a compromise must be found between the need of information, complexity of the measuring system and the related costs. Due to the difficulty in modelling most historical structures, it is a hard task to fix proper and safe limits relying on model-generated predictions only. The availability of long-term records of the structural response can help get this goal, not just relying on models, but also detecting changes in some parameters obtained from time records. This article presents a challenging example: the structural health monitoring of the Duomo di Milano main spire during and after restoration.